New isomer in 96Y marking the onset of deformation at N = 57. (28th February 2017) - Iskra, Ł. W.; Fornal, B.; Leoni, S.; Bocchi, G.; Petrovici, A.; Porzio, C.; Blanc, A.; De France, G.; Jentschel, M.; Köster, U.; Mutti, P.; Régis, J.-M.; et al.
Abstract: The level scheme of 96 Y was significantly extended and a new 201 ns isomer was located at 1655 keV excitation energy, with spin-parity assignment of 5 ± or 6 − . The isomer decays to spherical low-spin structure by transitions with large hindrance and is fed by a short cascade which resembles the beginning of a rotational band. This is in analogy with the feeding and decay pattern of the 4 − isomer in 98 Y, here confirmed, by lifetime analysis, as a bandhead of a rotational structure with sizable deformation. It is suggested that the new isomer in 96 Y arises from a shape change between deformed and spherical configurations, which indicates the appearance of deformation already at N = 57 in the yttrium chain. The experimental findings for 96 Y are strengthened by theoretical calculations based on the complex Excited Vampir model.